1981
DOI: 10.1007/bf01908163
|View full text |Cite
|
Sign up to set email alerts
|

The influence of reduced serum potassium level on the toxicity of some cardenolides in guinea pigs

Abstract: Recent experiments on the pharmacological properties of the semisynthetic cardiotonic steroid strophanthidin-3-bromoacetate (SBA) have challenged the well-known potassium digitalis antagonism in isolated heart muscle preparations. In order to establish these results in vivo, the minimum lethal doses (LDmin) of ouabain (OUA), digoxin (DO), digotoxin (DT), k-strophanthidin (STR) and SBA were determined by the infusion toxicity method in guinea pigs at normokalemia and hypokalemia. The experimentally induced decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For example, in rodents, despite their similar inotropic effects, ouabain and bufalin, but not digoxin, significantly shortened action potential duration (Kieval et al ., 1988; Ruch et al ., 2003); The LD 50 of ouabain and digoxin in rats is 14 and 32 mg·kg −1 respectively (Small et al ., 1971; Hovevey‐Sion and Kaplanski, 1979). However, a decrease in serum K + concentration significantly reduced the minimum lethal dose of digoxin but did not affect that of ouabain (Fricke and Klaus, 1981); bufalin produced a significant increase in heart rate (HR) whereas ouabain did not alter it (Pamnani et al ., 1991). Furthermore, digoxin even reduced cardiac rhythm (Segal et al ., 2000); The infusion of ouabain (Manunta et al ., 2000) and bufalin (Pamnani et al ., 1991) for several weeks produced hypertension in rats, whereas, digoxin did not exert such an effect (Huang et al ., 1999) or even caused a reduction in systemic blood pressure (BP) and prevented ouabain‐induced hypertension when given concomitantly (Manunta et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in rodents, despite their similar inotropic effects, ouabain and bufalin, but not digoxin, significantly shortened action potential duration (Kieval et al ., 1988; Ruch et al ., 2003); The LD 50 of ouabain and digoxin in rats is 14 and 32 mg·kg −1 respectively (Small et al ., 1971; Hovevey‐Sion and Kaplanski, 1979). However, a decrease in serum K + concentration significantly reduced the minimum lethal dose of digoxin but did not affect that of ouabain (Fricke and Klaus, 1981); bufalin produced a significant increase in heart rate (HR) whereas ouabain did not alter it (Pamnani et al ., 1991). Furthermore, digoxin even reduced cardiac rhythm (Segal et al ., 2000); The infusion of ouabain (Manunta et al ., 2000) and bufalin (Pamnani et al ., 1991) for several weeks produced hypertension in rats, whereas, digoxin did not exert such an effect (Huang et al ., 1999) or even caused a reduction in systemic blood pressure (BP) and prevented ouabain‐induced hypertension when given concomitantly (Manunta et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…2020). It is reported that [K + ] of guinea pig serum ranges from 4.8 to 5.2 mM (Fricke & Klaus, 1981). Therefore, one may argue that 5.9 mM [K + ] o could trigger ‘non‐physiological’ spontaneous activity via the depolarisation of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The bathing solution used in the present study contained 5.9 mM [K + ], which has been traditionally used in many studies on smooth muscle physiology (Smith et al 1987a,b;Kanai et al 2007;Baker et al 2013;Takeya et al 2017;Grainger et al 2020). It is reported that [K + ] of guinea pig serum ranges from 4.8 to 5.2 mM (Fricke & Klaus, 1981). Therefore, one may argue that 5.9 mM [K + ] o could trigger 'non-physiological' spontaneous activity via the depolarisation of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the ion bound within the site had a tremendous effect on CTS binding. Complexes with cardenolides (e.g., ouabain, digoxin) contained Mg 2+ , and substitution of Mg 2+ with K + or its congener Rb + induced a rearrangement of transmembrane helix 4 (αM4) whereby changing the position of the cardenolide in the site. , Functionally, it is manifested as a K + -induced decrease in affinity in vitro and described as an increased toxicity of digitalis under hypokalemic conditions in vivo . …”
Section: Introductionmentioning
confidence: 99%